Advanced problems in mechanics : proceedings of the XLVII International Summer School-Conference "Advanced Problems in Mechanics", June 24-29, 2019, St. Petersburg, Russia /: proceedings of the XLVII International Summer School-Conference "Advanced Problems in Mechanics", June 24-29, 2019, St. Petersburg, Russia. (2020) - Unknown
No abstract available